Evaluation of Facial Artery Musculomucosal Flap for Reconstruction of Small Tongue Defects - Kongara, Shruti; Purushothaman, Kishore; Mathew, Jimmy; Dhoke, Yogesh; Jaya, Arya Chandrababu; Galigutta, Srilekha Reddy; Rai, Shravan; Badam, Abhinandan; Thankappan, Krishnakumar; Iyer, Subramania (Indian Journal of Plastic Surgery, 2025)
Partial glossectomy defects can be managed by different methods, ranging from primary closure to pedicled or free flaps. The facial artery musculomucosal (FAMM) flap provides an excellent match to lingual tissue and provides an inconspicuous donor site. This study aims to compare functional outcomes, especially speech, of patients with partial glossectomy defects (≤1/3rd of tongue) reconstructed by FAMM flap with those of similar defects closed primarily or healed by secondary intention. It also offers to resolve the question of whether defects of this size should be reconstructed at all.A total of 25 patients with T1 or T2 oral tongue cancer undergoing resection and reconstruction with islanded FAMM Flap were included in the prospective limb of the study. Retrospective comparison was done with patients of similar defects who had primary closure (25 patients) or were allowed healing by secondary intention (25 patients). Their peri-operative parameters and functional outcomes were compared.The FAMM flap group required longer duration of nasogastric feeds and overall hospital stay. Speech intelligibility, as assessed by a speech therapist after 3 months, was satisfactory in all the groups of patients. Results of subjective assessment of speech-related problems did not demonstrate any advantage to the flap group.Patients with small tongue defects, irrespective of method of repair, have good speech outcomes. There was no significant difference between flap and non-flap groups in objective speech intelligibility outcomes. The benefit of reconstructing defects less than or equal to one-third of the tongue is questionable.
Keywords: tongue; glossectomy; speech intelligibility; facial artery musculomucosal flap